Pengaruh Jenis Hijauan Pakan dan Lama Penyimpanan Terhadap Sifat Fisik Wafer - Retnani, Yuli; Basymeleh, Suhail; Herawati, Lidy (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
The  aim  of  this  experiment  was  to  evaluate  the  effect  of  different  forage  wafer  variety,  storage periods  and  the  interaction  on  wafer  physical  characteristics.  The  experimental  design  used  in  this research was Factorial Completely Randomized Design with 2 factors and 4 replications. Factor A was forage variety composing wafer (R1 = 100% grass; R2 = 100 % maize straw; R3 = 100% maize steam, R4 = 50% field grass + maize straw; R5 = 50% field grass + maize steam; R6 = 50% maize straw + 50% maize steam. The variables  were water  content,  water activity  and density of wafer. Data collected was analyzed with ANOVA and Duncan Range Test would be used if the result was significantly different. The forage vaiety was very significant (P<0.01) on moisture content, water activity and density of wafer. The  storage  period  was  very  significantly  (P<0.01)  increasing  on  water  content,  water  activity  and decreasing  wafer  density.  There  was  very  significant  interaction  (P>0.01)  between  forage  variety  and storage period on water content, water activity and density of wafer.